Long-Read Isoform Sequencing Reveals a Hidden Complexity of the Transcriptional Landscape of Herpes Simplex Virus Type 1 - Tombácz, Dóra; Csabai, Zsolt; Szűcs, Attila; Balázs, Zsolt; Moldován, Norbert; Sharon, Donald; Snyder, Michael; Boldogkői, Zsolt (Frontiers in Microbiology, 2017)
In this study, we used the amplified isoform sequencing technique from Pacific Biosciences to characterize the poly(A)+ fraction of the lytic transcriptome of the herpes simplex virus type 1 (HSV-1). Our analysis detected 34 formerly unidentified protein-coding genes, ten non-coding RNAs, as well as 17 polycistronic and complex transcripts. This work also led us to identify many transcript isoforms, including 13 splice and 68 transcript end variants, as well as several transcript overlaps. Additionally, we determined previously unascertained transcriptional start and polyadenylation sites. We analyzed the transcriptional activity from the complementary DNA strand in five convergent HSV gene pairs with quantitative RT-PCR and detected antisense RNAs in each gene. This part of the study revealed an inverse correlation between the expressions of convergent partners. Our work adds new insights for understanding the complexity of the pervasive transcriptional overlaps by suggesting that there is a crosstalk between adjacent and distal genes through interaction between their transcription apparatuses. We also identified transcripts overlapping the HSV replication origins, which may indicate an interplay between the transcription and replication machineries. The relative abundance of HSV-1 transcripts has also been established by using a novel method based on the calculation of sequencing reads for the analysis.